Interpretation of Rahmatan lil-‘Alamin Verses: Foundations of Humanitarian-Based Character Education from the Perspective of the Qur’an and Pancasila - Solehah, Nur Zamro’atus; Shomad, Bukhori Abdul; Budimansyah, Budimansyah (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
This research aims to examine the values of Rahmatan lil-‘Alamin in the Qur’an and to analyze their relevance to character education based on humanity within the framework of Pancasila. The research employed a library research method with a tafsir maudhu’i (thematic exegesis) approach to Qur’anic verses related to Rahmatan lil-‘Alamin, complemented by analyses of classical and contemporary tafsir, academic literature, and relevant previous studies. The results of the research indicate that the values of Rahmatan lil-‘Alamin, including compassion (rahmah), justice (‘adl), tolerance, integrity, solidarity, and social responsibility, are substantially aligned with the second principle of Pancasila, namely Just and Civilized Humanity. The integration of Qur’anic values with Pancasila has practical implications for strengthening character education, which can be realized through contextual curriculum development, humanistic pedagogical approaches, teacher role modeling, and the establishment of an inclusive school culture. Therefore, this study affirms that the internalization of Qur’anic values and Pancasila can serve as a strategic foundation for shaping a generation that is morally upright, possesses integrity, shows empathy, and actively contributes to building a just, peaceful, and civilized Indonesian society.